PENERAPAN SANITATION AND HYGIENE DALAM PROSES PRODUKSI SAVORY CRABS DI UKM DesaKitara - Stephanie Bija; Novi Luthfiyana; Andi Ramadani; Heni Irawati; Maslan Maslan; Anhar Rozi; Burhanis Burhanis (Universitas Teuku Umar, 2022)
Savory crabs is a typical souvenir product of Tarakan city which was made from keraca crab raw materials. The processing of savory crabs must pay attention to sanitation and hygiene for producing safe products for consumption. Sanitation includes a clean and aseptic way of working, while hygiene is defined as the implementation of sanitation principles to maintain environmental health and cleanliness. The purpose of this activity was to know the implementation of sanitation and hygiene in the production process of savory crabs at UKM DesaKitara. The methods used were observation, interviews, socialization, evaluation and follow up. The aspects of sanitation and hygiene was observed include water safety, sanitation and hygiene of raw materials, sanitation and hygiene of workers, sanitation and hygiene of equipments, as well as sanitation and hygiene of end products. In addition, prevention of cross-contamination and waste handling are also observed.